2020
DOI: 10.1071/fp20127
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and facultative crassulacean acid metabolism (CAM) in Cuban oregano,

Abstract: Plants exhibiting the water-conserving crassulacean acid metabolism (CAM) photosynthetic pathway provide some of the most intriguing examples of photosynthetic diversity and plasticity. Here, a largely unnoticed facet of CAM-plant photosynthesis is highlighted: the co-occurrence of ontogenetically controlled constitutive and environmentally controlled facultative CAM in a species. Both forms of CAM are displayed in leaves of Coleus amboinicus Lour. (Lamiaceae), a semi-succulent perennial plant with oregano-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Crassulacean acid metabolism (CAM) is a photosynthetic pathway that has arisen convergently in many plant lineages, especially for the species that live in CO 2 and water-limited environments, such as some aquatic habitats, hot semiarid areas, and tropical forests [ 1 , 2 ]. Recent studies have revealed the multiple independent origins of the CAM pathway, which have occurred in at least 343 genera across 35 plant families, accounting for 6 percent of vascular plants [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crassulacean acid metabolism (CAM) is a photosynthetic pathway that has arisen convergently in many plant lineages, especially for the species that live in CO 2 and water-limited environments, such as some aquatic habitats, hot semiarid areas, and tropical forests [ 1 , 2 ]. Recent studies have revealed the multiple independent origins of the CAM pathway, which have occurred in at least 343 genera across 35 plant families, accounting for 6 percent of vascular plants [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper also contains an updated list of all plant families in which the CAM cycle has been confirmed. Winter et al (2021c) highlight the co-occurrence of both stress-induced facultative and developmentally controlled constitutive CAM in a species of the Lamiaceae, Coleus amboinicus Lour., which is widely cultivated in the tropics as a spice and ornamental plant. Holtum et al (2021) study CAM in two species of Cistanthe (Montiaceae) from the Atacama desert where these species contribute to spectacular desert blooms after rare massive rainfall events.…”
mentioning
confidence: 94%